Behavior of Polymer Modified Concrete Slabs under Impact - S. Al-Numan, Bayan; Ismail Al-Hadithi, Abdulkader (Iraqi Journal of Civil Engineering, 2008)
This research includes the study of improving impact resistance of concrete using styrene butadiene rubber (SBR) with different weight ratios of polymer to cement 3%, 5% and 10%. Two series of polymer modified concrete (PMC) were produced the first level I with moderate compressive strength and the other level II with higher compressive strength. Cubes, prisms and panels were made as follows: Results showed an improvement in impact resistance of polymer modified concrete (PMC) over reference concrete in low-velocity and high-velocity impact properties. In conducting low-velocity impact tests, method of repeated falling mass was used: 1300gm steel ball falling freely from three heights 2400mm, 1200mm and 830mm. In high-velocity impact tests, shooting of 7.62mm bullets was applied to slab specimens from distance of 15m. The improvements were significant in low velocity impact resistance. The maximum increases were (33.33%, 75% and 83.33%) at ultimate failure for falling mass heights 2400mm, 1200mm and 830mm respectively. In high-velocity impact strength tests, maximum reductions recorded in spalling area were (18.5% and 27%) for polymer modified concrete (level I) with moderate compressive strength and polymer modified concrete (level II) with higher compressive strength.Maximum reductions recorded in scabbing area were (11.42% and 35.6%) for polymer modified concrete (level I) with moderate compressive strength and polymer modified concrete (level II) with higher compressive strength, respectively.